Terminal ileum submucous plexus: Study of the VIP-ergic neurons of diabetic rats treated with ascorbic acid - Jacqueline Nelisis Zanoni; Luzmarina Hernandes; Roberto Barbosa Bazotte; Marcílio Hubner de Miranda Neto (Arquivos de Neuro-Psiquiatria)
The aim of this study was to evaluate the effect of the ascorbic acid (AA) supplementation on the neurons that produce the vasoactive intestinal peptide (VIP) in the submucous plexus of the ileum of rat, four months after the induction of experimental diabetes mellitus with streptozotocin. Three groups of rats were used: C - control, D - diabetic, DA - diabetic receiving AA. We have measured the immunoreactivity and area of 80 cellular bodies of VIP-ergic neurons from each studied group. In the diabetic animals, we have observed hyperphagia, polydipsia, and an increase of glycemia and glycated hemoglobin. The VIP-ergic neurons have presented an increase of their immunoreactivity and the highest profiles when compared to the other groups. In the diabetic animals supplemented with AA it has been observed a small reduction in the glycemia and the water and food intake. We have also noticed smaller immunoreactivity in their VIP-ergic neurons, similar to what we have observed in the control group animals (group C).